Fixed-width confidence interval of log odds ratio for joint binomial and inverse binomial sampling. Issue 3 (3rd July 2017) - Bandyopadhyay, Uttam; Sarkar, Suman; Biswas, Atanu
ABSTRACT: This article provides a two-stage procedure to develop a fixed-width confidence interval of log odds ratio in a joint binomial and inverse binomial setting where the stopping rule is obtained by adopting a two-stage procedure on the number of index subjects for the inverse sampling. A purely sequential version of this procedure is also studied. Different asymptotic results associated with the procedures are obtained. The findings are supported by detailed simulation study followed by one data example.